GENES IMPLICATED IN RESISTANCE TO SOYBEAN CYST NEMATODE INFECTION AND METHODS OF THEIR USE - KANDOTH, PRAMOD, KAITHERI; YECKEL, GREG; MITCHUM, MELISSA, GOELLNER; ITHAL, NAGABHUSHANA (2012)
To gain new insights into the mechanism of soybean resistance to the soybean cyst nematode (Heterodera glycines), gene expression profiles of developing syncytia in soybean near-isogenic lines (NILs) differing at the at Rhg1 locus were compared. Gene expression profiling revealed that 1,447 genes were differentially expressed between the line that is resistant to SCN and the line that is sensitive to SCN infection. These results indicate that syncytia induced in the resistant line are undergoing severe oxidative stress and imbalanced endoplasmic reticulum homeostasis, both of which likely contribute to the resistance reaction. Defense-related genes up-regulated within syncytia of the resistant line included those predominantly involved in apoptotic cell death, the plant hypersensitive response, and salicylic acid (SA)-mediated defense signaling; many of these genes were partially suppressed by a virulent soybean cyst nematode population for successful nematode reproduction and development on the resistant line. Expression of these SCN responsive genes may be manipulated to obtain SCN resistant lines. Pour acquérir de nouvelles connaissances en ce qui concerne le mécanisme de résistance du soja au nématode à kyste du soja (Heterodera glycines), on compare des profils d'expression génique de développement du syncytium dans des lignées de soja presque isogènes (NIL) différant au locus Rhg1. Les profils d'expression génique révèlent que 1447 gènes sont exprimés de manière différentielle entre la lignée qui est résistante au SCN et la lignée qui est sensible à l'infection du SCN. Ces résultats indiquent que le syncytium induit dans la lignée résistante subit un grave stress oxydatif et une hémostase du réticulum endoplasmique déséquilibrée, qui contribuent sans doute tous les deux à la réaction de résistance. Les gènes liés à la défense régulés positivement dans le syncytium de la lignée résistante incluent ceux impliqués de manière prédominante dans la mort des cellules apoptotiques, la réponse hypersensible de la plante, et la signalisation de la défense médiée par l'acide salicylique (SA) ; beaucoup de ces gènes sont partiellement supprimés par une population virulente de nématodes à kystes du soja pour la reproduction réussie des nématodes et le développement dans la lignée résistante. L'expression de ces gènes sensibles au SCN peut être manipulée pour obtenir des lignées résistantes au SCN.